Pathogenic variant profile in DNA damage response genes correlates with metastatic breast cancer progression-free survival in a Mexican-mestizo population - Vázquez-Romo, Rafael; Millan-Catalan, Oliver; Ruíz-García, Erika; Martínez-Gutiérrez, Antonio D.; Alvarado-Miranda, Alberto; Campos-Parra, Alma D.; López-Camarillo, César; Jacobo-Herrera, Nadia; López-Urrutia, Eduardo; Guardado-Estrada, Mariano; Cantú de León, David; Pérez-Plasencia, Carlos (Frontiers in Oncology, 2023)
Introduction Metastatic breast cancer causes the most breast cancer-related deaths around the world, especially in countries where breast cancer is detected late into its development. Genetic testing for cancer susceptibility started with the BRCA 1 and 2 genes. Still, recent research has shown that variations in other members of the DNA damage response (DDR) are also associated with elevated cancer risk, opening new opportunities for enhanced genetic testing strategies. Methods We sequenced BRCA1/2 and twelve other DDR genes from a Mexican-mestizo population of 40 metastatic breast cancer patients through semiconductor sequencing. Results Overall, we found 22 variants –9 of them reported for the first time– and a strikingly high proportion of variations in ARID1A. The presence of at least one variant in the ARID1A, BRCA1, BRCA2, or FANCA genes was associated with worse progression-free survival and overall survival in our patient cohort. Discussion Our results reflected the unique characteristics of the Mexican-mestizo population as the proportion of variants we found differed from that of other global populations. Based on these findings, we suggest routine screening for variants in ARID1A along with BRCA1/2 in breast cancer patients from the Mexican-mestizo population.